IMPLEMENTATION OF INNOVATION FOR PAI (ISLAMIC RELIGIOUS EDUCATION) TEACHER TO IMPROVE STUDENTS’ SPIRITUAL INTELLIGENCE: A CASE STUDY IN SCHOOL - Mohammad Jailani (Kementerian Agama Prov Jawa Tengah, 2024)
The purpose of this study was to determine the implementation of Islamic religious education, to determine the conditions of innovation that had been carried out by Islamic religious education teachers and to determine the supporting and inhibiting factors of Islamic religious education teacher innovation in developing students' spiritual intelligence. The method used in writing this research is the observation method, interview method and documentation method. while the author's data analysis using descriptive qualitative analysis. the results of the study concluded that: the implementation of Islamic religious education learning at SMK Negeri 1 Kebumen is quite good. The innovation that has been carried out by the teacher to develop students' spiritual intelligence is with learning media that is adapted to the method used. The driving and inhibiting factors of the innovation of Islamic religious education teachers in developing spiritual intelligence include: from students of different levels of intelligence, and awareness of the students themselves, while from the teacher because of the teacher's ability to create an interesting learning atmosphere and master many methods and adjust it, time, accuracy of media and learning methods.